REMOTE CONSEQUENCES OF PESTICIDE POLLUTION ON THE LEVEL OF DEVELOPMENT OF COGNITIVE FUNCTIONS - Kapysheva U. N.; Bakhtiyarova Sh. K.; Baimbetova A. K. (Academic Journal of Physical and Chemical Sciences, 2020)
The purpose of this study is to identify the characteristics of the state of short-term memory, sustainability and concentration of attention among rural residents living in places of long-term pesticidal pollution. The study of cognitive functions in residents was performed using the special Neurosoft computer base program. A significant decrease (by 20%) in the number of people with a high level of development of short-term memory by numbers and images was revealed. An increase of 18% in the number of people with poorly developed cognitive abilities is shown both when remembering information on numbers and images, as well as when concentration and stability of attention is on the desired object. At the same time, the memory capacity of residents with a high level of development of the function of memorizing information, both for numbers and images, was at the same level as the benchmarks and ranged from 61% to 67% of the amount of information proposed for memorization. The study showed that living in a zone of long-term pesticidal pollution worsens cognitive functions - memory and attention, upsets the balance of the main nervous processes - excitation and inhibition, and increases the risk of developing nervous disorders.